The Internet and “Frictionless Capitalism” - Jens Schröter (tripleC: Communication, Capitalism & Critique)
Since 1994 when the first browsers made their appearance the internet became the ‚new medium‘ par excellence. As is always the case with new media, there was an intense discussion about the future usage and effects of the new technology. One of the central arguments of this discussion was that the new medium might solve the problems of capitalism – Bill Gates coined the phrase "frictionless capitalism". In the first part of my paper some of these discourses are analyzed. These discourses, often publicly uttered by conservative and liberal politicians, try to construct the internet as commercial medium solving problems of late capitalism. But already the dotcom-crash 2001 hinted at problems with that construction. In the second part there is a discussion of a special interpretation of Marx’ theory of capitalist crisis. It is argued – also with recourse to Norbert Wiener – that the internet is part of the third industrial revolution which might lead to a very deep and even terminal crisis of capitalism. Instead of solving the problems of capitalism the internet might deepen them. We are witnessing since 2008 a chain of ever increasing symptoms of a deep crisis. By using Marx’ approach some of the important effects of the new medium can be described far more accurately than does the unreflected euphoria of Gates and others.